PENGEMBANGAN PRODUK BERBASIS RUMPUT LAUT BAGI MASYARAKAT PESISIR KABUPATEN KARAWANG - Pramono Adi, Catur (JURNAL KASTARA, 2022)
In 2021, the Fishery Product Processing Engineering Study Program of the Karawang Marine and Fisheries Polytechnic has carried out community service activities by applying the innovation of making seaweed soap products. The implementation of community service activities was carried out in Tambaksari Village, Tirtajaya District, Karawang Regency, Karawang Regency. Tambaksari village has great potential in the field of marine and fisheries, one of which is the availability of a wide area of seaweed ponds. The purpose of this community service activity is to improve the community's ability to process seaweed so that it can produce products with added value. Community Service Activities in 2021 by Lecturers of the Fishery Product Processing Engineering Study Program (TPPP) were carried out in the people of Tambaksari Village, Tirtajaya District, Karawang Regency on October 14, 2021. The implementation method was carried out through a lecture and practice-based approach, where this activity was carried out using demonstrations as media learning and practical activities accompanied by assistance, planning and monitoring and evaluation of all community service activities. There were 25 participants in this activity as a fulfillment of health protocols to prevent the transmission of COVID19. Each participant was given tools and materials to practice the manufacturing method demonstrated by the teaching team. Evaluation is carried out orally after the material is given to determine the extent to which participants can absorb the information provided.